Accuracy and Complication Rates of Maxillary Nerve Blocks: A Comparison of Techniques Using Surface Landmarks, Ultrasound and GPS‐Guidance. (September 2015) - Cordner, B.; Dixon, J.; Witte, T.
Abstract : Reasons for performing study: Perineural analgesia of the equine maxillary nerve is used for diagnostic and surgical procedures. Little data exists to evaluate accuracy and complication rates with current techniques. Objectives: This study compared 2 previously described approaches to maxillary nerve analgesia, and a novel needle guidance positioning system (SonixGPS™, Ultrasonix Medical Corporation, Richmond, British Columbia, Canada), assessing relative accuracy and complication rates of each method when performed by inexperienced operators. Study design: Cadaver study. Methods: Clinical veterinary students performed surface landmark, ultrasound and GPS guided contrast injections, to simulate maxillary nerve blocks in 38 equine cadaver heads. Computed tomography was then used to assess accuracy (successful deposition of contrast in contact with the maxillary nerve), and complication rate (contrast identified within surrounding vasculature or periocular structures), associated with each method. Results: Perineural injection of contrast around the maxillary nerve was attempted 76 times, with an overall success rate of 65.8% (50/76), and complication rate of 53.9% (41/76). Success rates were 50% (13/26) with surface landmark, 65.4% (17/26) with ultrasound and 83.3% (20/24) with GPS guided approaches (Fisher's exact P = 0.046). No significant difference in complication rate was found between the 3 methods. Conclusions: Ultrasound guided maxillary nerve blocks are significantly more accurate than surface landmark approaches when performed by inexperienced operators, and best success rates are achieved with GPS needle guidance. All 3 methods were equivalent in terms of complication rates when performed in cadavers. Ethical animal research:  This study was authorised by the Ethics and Welfare Committee of the Royal Veterinary College. The study was performed on material obtained from abattoirs.Source of funding:  Royal Veterinary College.Competing interests:  None declared.Acknowledgements:  We thank the technical teams of the Equine Referral Hospital Diagnostic Imaging and Pathology departments and the clinical veterinary students.